External beam radiotherapy and radical prostatectomy are associated with better survival in Asian prostate cancer patients - Würnschimmel, Christoph; Wenzel, Mike; Chierigo, Francesco; Flammia, Rocco Simone; Tian, Zhe; Saad, Fred; Briganti, Alberto; Shariat, Shahrokh F; Suardi, Nazareno; Terrone, Carlo; Gallucci, Michele; Chun, Felix Kh; et al. (International journal of urology, 2022)
OBJECTIVES: To test the effect of race/ethnicity on cancer-specific mortality after radical prostatectomy or external beam radiotherapy in localized prostate cancer patients. METHODS: In the Surveillance, Epidemiology and End Results database 2004-2016, we identified intermediate-risk and high-risk white (n = 151 632), Asian (n = 11 189), Hispanic/Latino (n = 20 077) and African American (n = 32 550) localized prostate cancer patients, treated with external beam radiotherapy or radical prostatectomy. Race/ethnicity-stratified cancer-specific mortality analyses relied on competing risks regression, after propensity score matching for patient and cancer characteristics. RESULTS: Compared with white patients, Asian intermediate- and high-risk external beam radiotherapy patients showed lower cancer-specific mortality (hazard ratio 0.58 and 0.70, respectively, both P ≤ 0.02). Additionally, Asian high-risk radical prostatectomy patients also showed lower cancer-specific mortality than white patients (hazard ratio 0.72, P = 0.04), but not Asian intermediate-risk radical prostatectomy patients (P = 0.08). Conversely, compared with white patients, African American intermediate-risk radical prostatectomy patients showed higher cancer-specific mortality (hazard ratio 1.36, P = 0.01), but not African American high-risk radical prostatectomy or intermediate- and high-risk external beam radiotherapy patients (all P ≥ 0.2). Finally, compared with white people, no cancer-specific mortality differences were recorded for Hispanic/Latino patients after external beam radiotherapy or radical prostatectomy, in both risk levels (P ≥ 0.2). CONCLUSIONS: Relative to white patients, an important cancer-specific mortality advantage applies to intermediate-risk and high-risk Asian prostate cancer patients treated with external beam radiotherapy, and to high-risk Asian patients treated with radical prostatectomy. These observations should be considered in pretreatment risk stratification and decision-making.
Keywords: lidé; Black or African American; prostata; other-cause mortality; prostatický specifický antigen; prostatektomie; Prostatectomy; Humans; Surveillance; Prostatic Neoplasms; černoši nebo Afroameričané; localized prostate cancer; mužské pohlaví; Prostate-Specific Antigen; nádory prostaty; Epidemiology and End Results; radical prostatectomy; cancer-specific mortality; Male; Prostate; external beam radiotherapy